Interactive Online Learning on Campus: Comparing Students' Outcomes in Hybrid and Traditional Courses in the University System of Maryland. (4th March 2017) - Chingos, Matthew M.; Griffiths, Rebecca J.; Mulhern, Christine; Spies, Richard R.
ABSTRACT: Massively open online courses (MOOCs) have received a great deal of attention, but little research exists on how they might fit into the existing system of higher education. We studied the impacts on learning outcomes of hybrid courses redesigned using online materials from MOOCs created on the Coursera platform and digital materials created by the Open Learning Initiative (OLI), relative to existing versions of the same courses. We found that student performance was about the same in both sections, as measured by pass rates and scores on common assessments. This finding held across a variety of disciplines and subgroups of students. We found no evidence supporting the worry that disadvantaged or academically underprepared students were harmed by taking hybrid courses with reduced class time. Despite the similar student outcomes produced by the two course formats, students in the hybrid sections reported considerably lower satisfaction with their experience.